Association between immune cells and allergic purpura: a Mendelian randomization study - Wei Xian; Huiyi Zhang; Huasong Zeng (Italian Journal of Pediatrics)
Abstract Background Increasing evidence indicates a substantial correlation between the immune cells and the risk of allergic purpura. We utilized Mendelian randomization (MR) to investigate causal effect of immune cell on allergic purpura. Methods Genetic instrumental variables for immune cells were sourced from an extensive genome-wide association study (GWAS) comprising 3757 participants. Summary statistics of allergic purpura, involving 470 cases and 216,099 controls, were obtained from FinnGen. The primary analysis employed the inverse-variance weighted (IVW) method. Rigorous sensitivity analyses including MR-Egger, weighted median and MR-PRESSO were conducted to ensure the reliability of the causal estimate. Results We identified two immunophenotypes associated with an increased risk of allergic purpura: HLA-DR on CD14 + CD16- monocyte (OR: 1.2379; 95% CI: 1.0612–1.4440; P = 0.0066) and CD11b on basophil (OR: 1.2973; 95% CI: 1.0905–1.5433; P = 0.0033). The sensitivity analyses consistently yielded similar results for these immunophenotypes. Conclusions Our analyses confirmed a potential causal effect of HLA-DR on CD14 + CD16- monocyte, as well as CD11b on basophils, in relation to the risk of allergic purpura. Further studies are necessary to clarify the mechanisms by which these immunophenotypes influence the development of allergic purpura.